2018
DOI: 10.11606/s1518-8787.2018052000264
|View full text |Cite
|
Sign up to set email alerts
|

General and abdominal obesity in adults living in a rural area in Southern Brazil

Abstract: OBJECTIVETo evaluate the prevalence of general and abdominal obesity and the concomitant presence of both outcomes and their determinants among adults living in a rural area.METHODSThis cross-sectional, population-based study was carried out in a medium-sized city in the southern region of Brazil. We evaluated three outcomes: general obesity (body mass index ≥ 30 kg/m 2 ), abdominal obesity (waist circumference ≥ 102 cm and ≥ 88 cm in men and women, respectively), and concomitant obesities, classified as: no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
(25 reference statements)
5
8
0
1
Order By: Relevance
“…Regarding abdominal obesity, the lack of large surveys in rural areas restricts the possibility of comparisons. However, the findings of this study are in agreement with the high prevalences reported in specific studies for Brazilian rural areas, varying from 11.6% in the Southeast Region (Minas Gerais) 28 to 37.8% in the South Region (Pelotas) 22 . A study conducted with women in the South Region of the country (Catuípe) 5 showed an even higher prevalence of abdominal obesity, 54.6%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding abdominal obesity, the lack of large surveys in rural areas restricts the possibility of comparisons. However, the findings of this study are in agreement with the high prevalences reported in specific studies for Brazilian rural areas, varying from 11.6% in the Southeast Region (Minas Gerais) 28 to 37.8% in the South Region (Pelotas) 22 . A study conducted with women in the South Region of the country (Catuípe) 5 showed an even higher prevalence of abdominal obesity, 54.6%.…”
Section: Discussionsupporting
confidence: 92%
“…In this survey, prevalences in urban areas reached 13.2% for men and 17.0% for women, while prevalences in rural areas reached 8.8% and 16.5%, respectively, for men and women. Moreover, the prevalence of general obesity described in this study for the rural area is in agreement with the few studies carried out in rural areas of Brazil (varying from 5.5% in Minas Gerais 21 to 29.5% in Rio Grande do Sul 22 ), in the United States (39.6 to 45.7%) 23,24 , Turkey (30.3%) 25 , South-Eastern Limestone Coast region in Australia (30.0%) 26 , and South Africa (27.2%) 27 . When stratified by region, the results resemble those of the Household Budget Survey in 2008-2009 20 , which reported higher prevalences of general obesity in the urban area of the South Region in men (16.4%) and women (19.3%).…”
Section: Discussionsupporting
confidence: 92%
“…However, rural areas differ from urban areas in many aspects that are difficult to measure in population studies, such as sociodemographic, socioeconomic and cultural factors [ 23 ], and therefore, surveys that evaluate these particularities are necessary. Additionally, labor aspects in these rural areas have been minimally explored, even though it is a possible determinant of obesity in rural areas [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural productivity is essential to sustaining the nutritional and health status of billions of people [3], and small farmers are critical to the global food supply [4]. However, agriculture is a dangerous profession [5] and with priority of attention [6], due to its occupational health risks and the presence of non-communicable chronic diseases and their risk factors [7][8][9][10][11].…”
mentioning
confidence: 99%
“…Despite the finding of an increase in the morbidity and mortality profile of this population [7][8][9][10][11], representative research on the food consumption of farmers and the rural population is still scarce [18], especially studies developed with the purpose of studying the dietary patterns of these populations and their associated factors [4][5][6][19][20][21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%